Influence of Grassland Habitats on Acridoidea (Orthoptera) Species Diversity in Different Divisions of the Xinjiang Production and Construction Corps - Yuxian Liu; Shaoshan Wang; Yuheng He; Guanzheng Yuan; Xingyu Pu; Chao Zhou (Biology)
In this study, we investigated Acridoidea species and their populations in the grasslands managed by 13 divisions of the Xinjiang Production and Construction Corps (hereafter referred to as the Corps) during 2022–2024. We analyzed how the Corps’ grassland habitats influenced Acridoidea diversity. Using the netting method, we collected 5290 Acridoidea specimens, representing eight families, 37 genera, and 83 species. The Acridoidea were most abundant in mountain meadows and temperate grasslands, with 42 and 43 species, respectively, while the species richness in temperate desert grasslands and temperate steppe desert grasslands was comparably high. The highest diversity index of Acridoidea was recorded in temperate grasslands (3.053), followed by mountain meadows (2.563). Regarding altitude, the diversity index was highest in the 1000–1500 m range (3.237), followed by 500–1000 m (2.976) and 1500–2000 m (2.867). However, above 1500 m, the diversity index began to decline. The Acridoidea species diversity was significantly positively correlated with the average temperatures of the wettest and warmest seasons, as well as with precipitation levels during the wettest and driest months. The dominant grassland Acridoidea species were primarily distributed in areas with low-to-medium-low soil erodibility. These findings indicate that grassland types, elevation, temperature, humidity, and soil erodibility significantly influence Acridoidea habitats, survival, reproduction, and feeding behaviors, ultimately shaping their composition, distribution, and abundance across different habitats.